Dynamic balance ability in young elite soccer players: implication of isometric strength - Chtara, M.; Rouissi, M.; Bragazzi, N. L.; Owen, A. L.; Haddad, M.; Chamari, K. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Soccer requires maintaining unilateral balance when executing movement with the contralateral leg. Despite the fact that balance requires standing with maintaining isometric posture with the support leg, currently there is a lack of studies regarding the implication of isometric strength on dynamic balance's performance among young soccer players. Therefore, the aim of this study was to examine the relationship between the Y-Balance Test and 12 lower limbs isometric strength tests.